PENGARUH MEDIA PEMBELAJARAN INTERAKTIF BERBASIS APLIKASI GENIALLY PADA MATERI BHINEKA TUNGGAL IKA TERHADAP HASIL BELAJAR KOGNITIF SISWA KELAS X SMA NEGERI 2 BINJAI T.A 2025/2026 - Sati Sintania, Laras; Yunita, Sri; Nainggolan, Mangido; Rachman, Fazli; Habeahan, Sampitmo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using interactive learning media based on the Genially application on students' cognitive learning outcomes in the Bhinneka Tunggal Ika material in Grade X of SMA Negeri 2 Binjai. This research was motivated by the dominant use of conventional teaching methods in Pancasila Education subjects and the low level of student engagement during the learning process. The use of interactive digital media such as Genially is expected to increase students' motivation, participation, and understanding of the learning material. This study employed a quantitative approach using the True Experimental Design method with a Pre-test and Post-test Control Group Design. The population consisted of all Grade X students of SMA Negeri 2 Binjai in the 2025/2026 academic year, totaling 378 students. The sample consisted of 64 students, with Class X-4 serving as the experimental group and Class X-5 as the control group, each consisting of 32 students. Data were collected through pre-test and post-test instruments. Data analysis was conducted using the normality test, homogeneity test, and Independent Sample T-Test. The results showed that the average post-test score of the experimental group was 76.94, which was higher than that of the control group at 70.05. The hypothesis testing result obtained a significance value of 0.001 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. Therefore, the use of interactive learning media based on the Genially application has a significant effect on students' cognitive learning outcomes.